2019
DOI: 10.1186/s40468-019-0097-4
|View full text |Cite
|
Sign up to set email alerts
|

Writing scale effects on raters: an exploratory study

Abstract: In writing assessment, finding a valid, reliable, and efficient scale is critical. Appropriate scales, increase rater reliability, and can also save time and money. This exploratory study compared the effects of a binary scale and an analytic scale across teacher raters and expert raters. The purpose of the study is to find out how different scale types impact rating performance and scores. The raters in this study rated twenty short EFL essays using the two scales, completed a rater cognition questionnaire, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…According to the observations, raters felt more confusion in their ratings which implied that they got it quite demanding to clearly select one level. This finding is in line with Jeong (2019) who concluded that raters had to consider multiple areas in the analytic rating process and experienced more hesitation and rating conflict. Therefore, these strategies like anchoring happened more in analytic evaluations which can be due to the vague wording of the scale.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…According to the observations, raters felt more confusion in their ratings which implied that they got it quite demanding to clearly select one level. This finding is in line with Jeong (2019) who concluded that raters had to consider multiple areas in the analytic rating process and experienced more hesitation and rating conflict. Therefore, these strategies like anchoring happened more in analytic evaluations which can be due to the vague wording of the scale.…”
Section: Discussionsupporting
confidence: 89%
“…Thanks to this, it might be difficult for raters to analyze and interpret the scale components, and through adopting those strategies, they lessened the cognitive load. On the other hand, findings of Jeong ( 2019 ) showed that the scale design has a greater effect on the raters. Thus, designing rating scales and the rating criteria should provide an explicit and reliable foundation for scoring judgments, over and above distinguishing writing performance levels (Weigle, 2002 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…One examines rater scores quantitatively to detect rater effects; the other examines rater behavior qualitatively to explain how rater effects arise. Rating scores are typically analyzed by MFRM analysis (Jeong, 2019; Myford & Wolfe, 2003; Schaefer, 2008; Trace et al, 2017; Wang et al, 2017). Its central idea is to model many facets (e.g., examinee, criterion, and rater) in the rating process to predict the probability of a particular rating.…”
Section: Current Approaches To Examining Rater Scores and Rater Behaviormentioning
confidence: 99%
“…Whereas the former represents the product of scoring, the latter evidences the process of scoring (Greene et al, 1989). Rater scores are typically examined through many-facet Rasch measurement (MFRM) (e.g., Jeong, 2019; Myford & Wolfe, 2003; Schaefer, 2008), while rater behavior tends to be examined through surveys and/or interviews (e.g., Jeong, 2019), think-aloud protocols (e.g., Barkaoui, 2007), rater comments (e.g., H. J. Kim, 2015), or eye-tracking experiments (e.g., Ballard, 2017; Winke & Lim, 2015).…”
mentioning
confidence: 99%